Eye of the Beholder: Memory Recall Perspective Impacts Nostalgia’s Influence on Positive Affect - Rogers, Ross (Frontiers in Psychology, 2020)
Recalling memories for which one is nostalgic provides a host of psychological benefits, including promoting positive affect. The present research (N = 409) examined how memory recall perspective impacts this affective consequence of waxing nostalgic. Memory recall perspective research indicates that people show stronger affective engagement with memories recalled from a 1st person perspective (seeing the event through one’s own eyes, as one experienced it) rather than a 3rd person perspective (seeing the event as an outside observer may have). Results indicated that when participants recalled memories from a 1st person perspective, those who recalled an event for which they felt nostalgic reported higher positive affect compared to their counterparts who recalled an ordinary past event. However, when participants recalled memories from a 3rd person perspective, those who recalled an event for which they felt nostalgic reported levels of positive affect that did not differ from participants who recalled an ordinary past event. This finding suggests that, when comparing nostalgic reverie to recalling an ordinary past event, the extent to which nostalgia serves as a well-spring of positive affect is partially impacted by memory recall perspective.